3D printed bioceramic scaffolds: Adjusting pore dimension is beneficial for mandibular bone defects repair. (14th February 2022) - Qin, Hongling; Wei, Yingming; Han, Jiayin; Jiang, Xiaojian; Yang, Xianyan; Wu, Yanmin; Gou, Zhongru; Chen, Lili
Abstract: Bioceramic scaffolds for repairing mandibular bone defects have considerable effects, whereas pore architecture in porous scaffolds on osteogenesis in specific structures is still controversial. Herein 6 mol% magnesium‐substituted calcium silicate scaffolds were fabricated with similar porosity (∼58%) but different cylindrical pore dimensions (Ø 480, 600, and 720 μm) via digital light processing‐based three‐dimensional (3D) printing technique. The mechanical properties, bioactive ion release, and bio‐dissolution of the bioceramic scaffolds were evaluated in vitro, and the facilitation of scaffolds on bone formation was investigated after implanting in vivo. The results showed that as the pore dimension increased, the scaffolds indicated similar surface microstructures, but their compressive strength was enhanced gradually. There was no significant difference in vitro bio‐dissolution between the 480 and 600 μm groups, whereas the 720 μm group showed a much slower dissolution and ion release. Interestingly, the two‐dimensional/three‐dimensional (2D/3D) micro‐CT reconstruction analysis of rabbits' mandibular bone defects model showed that the 600 μm group exhibited evidently higher ratio of the newly formed bone volume to total volume (BV/TV) and trabecular number (Tb. N) values and lower ratio of the scaffolds residual volume to total volume (RV/TV) compare to the other two sizes. Furthermore, the histological analysis also revealed a considerably higher new bone ingrowth rate in the 600 μm group than the other two groups at 4–12 weeks post‐implantation. Totally, it is proved from these experimental studies that the DLP‐based accurately fabricated calcium (Ca) silicate bioceramic scaffolds with appropriate pore dimensions (i.e., 600 μm in pore size) are promising to guide new bone ingrowth and thus accelerate the regeneration and repair of cranial maxillofacial or periodontal bone defects.